Lignin-Carbohydrate Complexes Based Spherical Biocarriers: Preparation, Characterization, and Biocompatibility - Houkuan Zhao; Jinling Li; Peng Wang; Shaoqiong Zeng; Yimin Xie (International Journal of Polymer Science)
Spherical biocarriers were prepared with lignin-carbohydrate complexes isolated from ginkgo (Ginkgo biloba L.) xylem. The specific surface and average pore size of the biocarriers were 17.15 m2 g−1 and 21.59 nm, respectively. The carriers were stable in solution at pH 4.0~9.5. Fourier transform infrared (FT-IR) spectrum indicated that the spherical carrier was composed of lignin and polysaccharides and had a typical lignin-carbohydrate complex (LCC) structure. The contents of galactose, lignin, and total sugar were 3.30%, 23.9%, and 64.62%, respectively, making the spherical biocarriers have good physical strength and compatible with hepatocytes. It was observed using a scanning electron microscopy (SEM) that liver cells adhered to the spherical biocarriers during culture. Cell counting indicated that the proliferation of liver cells in the experimental group was significantly higher than that of the control group. The albumin secretion (ALB) value and glucose consumption of the human hepatocytes were increased by 51.7% and 38.6%, respectively, by the fourth day when cultivated on the biocarriers. The results indicate that ginkgo LCC is very biocompatible and shows promise for the use as a biomaterial in the culture of human hepatocytes.